A Study of the Cereal Benches Based System for Protection of Soil in Algerian Oued Mellegue Tebessa Dry Lands - Mourad Douh; Larbi Karkour; Samir Chakchaki; Laid Bouchaala; M. Mokdad (Annals of Arid Zone, 2024)
The study was intended to mitigate the destructive after-effects of erosion, where runoff water erodes the arable layers through the increased transport of soil particles. The study was conducted in Ain Zerga across 40 plots, covering an area of 405 hectares, during 2023 and 2024, with a focus on the dimensional evaluation of cereal beds. The evaluation mainly focused (a) on the durability of the structure, including the measurement of settlement, which indicates distribution and strength of resistance to climatic hazards, and (b) proportional sustainability and the interbank aspects. The height of benches, at 0.481± 0.086 m, and the length of 82.583 ± 24.203 m were influenced by height differences and the intensity of water flows. The retention of runoff water was influenced by the slope toward the natural spillway. Furthermore, the destructive intensity of the runoff, amplified by the sharp increase in altitude, was confirmed by statistically significant differences in the length, height, and number of cracks between the study sites (p-value = 0.000). The number of cracks per breach at the Gastel site (4.25 units) and Kef Mebdoua (3.917 units) was higher compared to Ain Zerga, Berket Frass, Ouled Mebarek, and Zlassde, where the number ranged from 0.750 to 1.583 units. The statistical significance in the number of cracks (p<0.001) signified that variation in cracks between the locations was due to the topographic steep slopes on site. The non-significant difference in width suggests that the observed differences could be due to the phenomenon of compaction following the annual infiltration of water on the ridges of cereal bench, plus the act of trampling constantly exercised by sheep and cattle herds when passing to the paths. This work proposed in this article is an attempt to structure a chain of impact analysis of risks and vulnerability of intensity via the sustainability of cereal bench carried out in the Tebessa region.